ALTERNATIVE GELLING AGENTS FOR IN VITRO PROPAGATION OF ORCHID (DENDROBIUM SONIA) - M. A. Ullah; M. I. Uddin; A. B. Puteh; M. S. Haque; M. S. Islam (Journal of Animal and Plant Sciences, 2015)
We investigated the appropriate growth conditions of shoot and root through in vitro propagation of orchid (Dendrobium sonia) using different gelling agents. Protocorm Like Bodies (PLBs) of orchid were initiated earlier in vitro and one month old protocorms were used for this study. Protocorms were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations of starches viz. isubgol (15, 20, 25 and 30gL-1), cassava (15, 20, 25 and 30gL-1), corn (50 and 60gL-1) and potato (50 and 60gL-1) used as alternative gelling agents as compared with 8gL-1 agar at different stages at 35, 70 and 105 days. The MS medium supplemented with the increasing dose of isubgol, cassava, corn and potato gelled with 2gL-1 agar progressively increased their growth performance. The best performance on growth of shoots leaves and roots were recorded at 30gL-1 isubgol when isubgol used as an alternative gelling agent on agar. The use of 30gL-1 isubgol (500g costs US$ 10 only) was very much cheaper than conventionally used agar. The present study offers a new possibility of using low cost alternative gelling agent which will reduce the production costs considerably plant tissue culture techniques.
Keywords: Alternative gelling agent; Dendrobium sonia; Orchid propagation; Isubgol